2021
DOI: 10.1111/jonm.13449
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours and experiences of nurses during the COVID‐19 pandemic in Turkey: A mixed methods study

Abstract: Aim The aim of this work is to present behaviours and experiences of nurses in Turkey during the current coronavirus pandemic. Background The coronavirus pandemic leads to difficulties for most health care workers, especially for nurses who mostly accompany patients and are on the front line. Methods In the study, a parallel mixed pattern converging quantitative and qualitative research methods was used. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
1
33
0
3
Order By: Relevance
“…The unknown nature of the virus created a strong fear of infection among participants in this study. This feeling is emphasised by nurses in other qualitative studies from the pandemic, who also describe fear intensified by the tenuous nature of PPE—of inadequate quantity (as described in this study) but additionally of uncertain quality 26 28 30–32 37–39. Literature from this pandemic and previous disease outbreaks suggests that the frontline nature of their role may place nurses at higher risk of physical and psychological distress than other healthcare professions 26 32 33.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The unknown nature of the virus created a strong fear of infection among participants in this study. This feeling is emphasised by nurses in other qualitative studies from the pandemic, who also describe fear intensified by the tenuous nature of PPE—of inadequate quantity (as described in this study) but additionally of uncertain quality 26 28 30–32 37–39. Literature from this pandemic and previous disease outbreaks suggests that the frontline nature of their role may place nurses at higher risk of physical and psychological distress than other healthcare professions 26 32 33.…”
Section: Discussionmentioning
confidence: 58%
“…This study found that the COVID-19 pandemic has been a stressful period for nurses and HCAs in general practice, aligning with international accounts of primary care25 27 29 35–37 39 56–58 and nurses’ experiences in general 26 28 30–34 40 59–62. The necessity for meaningful and accessible short-term and long-term mental health support and continuous education and training are key recommendations in the literature 21–23 25 28 31 32 37 38 40 57 59. However, this study emphasised additional measures that could help to better support primary care nurses, HCAs and the wider primary care team.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It was found that 85.0% of the participants followed the quarantine rules, 75.7% paid attention to social distancing while working and 81.7% followed the social distance rule in the places where they ate. It was found that 46.7% of the participants feared that they might be carriers of COVID-19 and 38.9% feared COVID-19 infection [ 27 ]. In a study by Sikaras et al, 52.4% of the respondents worked in COVID-19 units, the results of 67.9% and 42.9%, respectively, suggested the occurrence of fatigue and burnout among them and showed a strong positive correlation ( p < 0.01, r = 0.70) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%